Efektivitas Pelayanan Paspor Menggunakan Aplikasi Mobile Paspor di Kantor Imigrasi Kelas I TPI Palembang - Sofyandani, Albima Umari; Idi, Abdullah; Mardianto, Mardianto (@-Publik: Jurnal Administrasi Publik, 2023)
This research concerns the effectiveness of passport services using the mobile passport application at the Class I Immigration Office TPI Palembang. The background of this research is that there are still problems with passport services at the Class I Immigration Office TPI Palembang. The purpose of this study was to analyze the Effectiveness of Passport Services using the Mobile Passport Application at the Class I Immigration Office TPI Palembang. This study uses the effectiveness theory of Martani and Lubis regarding organizational effectiveness. The dimensions are the target approach, source approach and process approach. This research was conducted using a qualitative method and a descriptive approach. Data collection techniques with the method of observation, semi-structured interviews and documentation. In order to obtain the level of confidence in research data or the level of significance of a study, steps to test the validity of the data were carried out by means of data condensation and verification of the data obtained. As for the results of the analysis of this study it can be concluded that the effectiveness of passport services using the mobile passport application at the Immigration Office Class I TPI Palembang as measured using the target approach, source approach and also the process approach is not yet effective.